If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(2x+4)=(2x+5)
We move all terms to the left:
(2x+4)-((2x+5))=0
We get rid of parentheses
2x-((2x+5))+4=0
We calculate terms in parentheses: -((2x+5)), so:We get rid of parentheses
(2x+5)
We get rid of parentheses
2x+5
Back to the equation:
-(2x+5)
2x-2x-5+4=0
We add all the numbers together, and all the variables
-1!=0
There is no solution for this equation
| -2z+11=36,6 | | 39(x+2)+x=4(x-1)+10 | | 5y-6=2y-42 | | 3(x-2)=3x-4 | | 5x+52=3x-16 | | 12,4=6a-2 | | 6x-(2x-9)=-31 | | 61y-15=-137 | | 122=2w+35 | | 8w-18=14 | | 16x-3=269 | | 10x+1=12x+7 | | 10x+-1=12x+7 | | 8+2(x-6)0=-2+2x-2 | | 3v+15=33 | | -24=2(x+5) | | x(3x-12)=96 | | 13x+5=8x-+14 | | x+8=2x+10 | | -4w-5=-41 | | -7(-4-6j)=2+194 | | F(x)=3/x+2 | | 10=p/2-2 | | -3c=-18.9 | | 2(2x-1)=(x+1 | | 369-18=-9(-3-4v) | | t−14=-12.5 | | 28=-7(2z+4) | | 14z=616 | | 16p=432 | | x-8+3x=4(x-2) | | n17=16 |